Insights into suckling rabbit feeding behaviour: acceptability of different creep feed presentations and attractiveness for sensory feed additives. (13th February 2020) - Paës, C.; Fortun-Lamothe, L.; Coureaud, G.; Bébin, K.; Duperray, J.; Gohier, C.; Guené-Grand, E.; Rebours, G.; Aymard, P.; Bannelier, C.; Debrusse, A. M.; Gidenne, T.; et al.
Abstract : In young rabbit, digestive disorders are frequently observed around weaning. Stimulating the onset of feed intake in the suckling rabbit might be a way to promote gut health. The aim of this study was to determine the rabbit's acceptability for different feed presentations and its preferences for flavours at an early stage of life. Two trials were conducted to evaluate the effects of physical form and flavouring on creep feed attractiveness. All the diets tested were provided in the nest from 3 to 17 days, and the daily intake per litter was recorded as of 8 days of age. In the first trial, five feed presentations were tested separately ( n = 60 litters). Three dry presentations were chosen: commercial pellet (P), crumb from commercial pellet (cP) and crumb from beet pulp pellet (cBP). Hydrated feeds were also provided with either raw fodder beetroot (B) or a semi-solid feed in agar gel form produced with fodder beetroot juice and pulp (gB). In the second trial, double-choice tests were performed on four feed gels ( n = 72 litters), leading to six comparison treatments. These agar gels were made of pellet mash without or with a sensory additive: one non-odorised control gel and three gels with 0.20% banana flavour, 0.06% red berry flavour and 0.10% vanilla flavour, respectively. In the first trial, kits ate more gB in fresh matter than other feed presentations ( P < 0.001), with a total intake of 7.0 ± 1.8 g/rabbit from 8 to 17 days. In DM, the total consumption of pellets P (1.6 ± 0.4 g of DM/rabbit) was the highest together with the gB form (1.4 ± 0.4 g of DM/rabbit), whereas cBP was barely consumed (0.3 ± 0.1 g of DM/rabbit). Gel feed supplemented with vanilla was slightly more consumed than other flavoured and non-odorised gels (relative consumption of 57% when compared to control gel; P = 0.001). The gel feed intake was independent of the milk intake but was correlated with the litter weight at 3 days ( r = 0.40, P < 0.001). In both trials, rabbit growth before and after weaning was not affected by the type of creep feed provided. Our results confirmed that providing creep feed promotes the solid intake of rabbits at early stages. Gel feed form motivated rabbits to eat and vanilla flavour supplementation increased the feed palatability. Those creep feed characteristics should be explored further for seeking effective stimulation of the onset of the feed intake in suckling rabbit.